Experimental Confirmation of a Predicted Porous Hydrogen‐Bonded Organic Framework - Shields, Caitlin E.; Wang, Xue; Fellowes, Thomas; Clowes, Rob; Chen, Linjiang; Day, Graeme M.; Slater, Anna G.; Ward, John W.; Little, Marc A.; Cooper, Andrew I. (Angewandte Chemie International Edition, 2023)
Hydrogen‐bonded organic frameworks (HOFs) with low densities and high porosities are rare and challenging to design because most molecules have a strong energetic preference for close packing. Crystal structure prediction (CSP) can rank the crystal packings available to an organic molecule based on their relative lattice energies. This has become a powerful tool for the a priori design of porous molecular crystals. Previously, we combined CSP with structure‐property predictions to generate energy‐structure‐function (ESF) maps for a series of triptycene‐based molecules with quinoxaline groups. From these ESF maps, triptycene trisquinoxalinedione (TH5) was predicted to form a previously unknown low‐energy HOF (TH5‐A) with a remarkably low density of 0.374 g cm−3 and three‐dimensional (3D) pores. Here, we demonstrate the reliability of those ESF maps by discovering this TH5‐A polymorph experimentally. This material has a high accessible surface area of 3,284 m2 g−1, as measured by nitrogen adsorption, making it one of the most porous HOFs reported to date. A hydrogen‐bonded framework that was predicted previously to have 3D porosity and a remarkably low density of 0.37 g cm−3 has been discovered experimentally. The structure of this framework matches the original prediction precisely and it has an accessible surface area of 3,284 m2 g−1, as measured by nitrogen adsorption, making it one of the most porous hydrogen‐bonded frameworks synthesized to date.